Pengaruh Kompetensi Bahasa Inggris terhadap Produktivitas - Ariansyah, Aldi; Caesar, Linggar (Journal of Information Systems and Management (JISMA), 2024)
English is an international language that is often used by many people in the world, both for business, education and daily conversations. Because of this, many countries are practicing English as their second language. Based on a report by the educational institution Education First (EF), Indonesia has an English proficiency index of 466 in 2021. This score is in the low proficiency category and makes it fifth in Southeast Asia. . The aim of this study is to determine the effect of foreign language competency on increasing productivity. as well as analyzing the influence of effective communication in a foreign language which influences collaboration, coordination and effectiveness in a multicultural environment. In this study report, a descriptive qualitative method is used by taking notes because the data source was obtained by listening to oral narratives from the CAKAP YouTube channel entitled " Gita Wirjawan: The More You Can Communicate, The More You Can Increase Productivity in the Future" explained by the Former Minister of Trade of the Republic of Indonesia, namely Gita Wirjawan. The results of this study explain the importance of communication for each individual so that it can increase productivity in career, business and everyday life.